Surgical Embolectomy In Massive Acute Pulmonary Embolism: Our Experience - Nemirova, SV; Medvedev, AP; Pichugin, VV; Bhandari, Krishna (Nepalese Heart Journal, 2015)
Background and Aims: Pulmonary embolism (PE) is the leading cause of hospital deaths among the non-surgical patients. Our aim was to evaluate the efficacy of surgical embolectomy in massive acute PE. Methods: It was a single centre, prospective study conducted between January 2007 and August 2013 in Specialized Cardiovascular Surgical Hospital of Nizhny Nizhny Novgorod State Medical Academy Nizhny Novgorod, Russia. One hundred and seventy five patients were diagnosed as PE. Only 77 patients were diagnosed as massive pulmonary embolism and were included in this study. Surgical embolectomy was performed without cardiopulmonary bypass through thoracotomy approach only in the involved pulmonary artery. Right atriotomy and evacuation of embolus was done, in cases of right ventricle thrombus. Results: Seventy-seven patients with acute massive PE underwent surgical embolectomy. Four (5.1%) patients died before discharge. Mean time of ICU stay was 70.1±11.0 hours. During six months of follow up after the embolotomy. Eleven (14%) patients had deep vein thrombosis, two had sub-massive PE. During 6 months of follow up 62 patients (81%) had no further episode of venous thrombloembolism. Conclusions: Our study showed surgical embolectomy can be done with good clinical outcome with acceptable mortality rate. Nepalese Heart Journal 2015;12(2):83-86